Student Satisfaction with Blended Learning: An Online Survey in a Vietnamese University - Phuong, Bui Thi Kim; Anh, Bui Thi Van (VNU Journal of Science: Education Research, 2023)
Blended learning has been widely applied in Vietnamese higher education in recent years. In blended learning, student satisfaction is regarded as a decisive factor in assessing whether blended learning courses are successful or not. This paper assesses the students' satisfaction with a blended English language learning course and with four groups of criteria, including course contents, teaching methods, exercises on LMS (Learning Management System), and assessment tasks. An online survey with 250 students from a Vietnamese university reveals that students have a high level of satisfaction with the course and other criteria. Furthermore, a strong linear relationship has been identified between the overall satisfaction of the whole course and the students’ progress after the course. The findings are expected to promote and improve blended learning practices in Vietnam universities with practical implications for course developers and other stakeholders.